The response and coupling coordination of soil moisture to vegetation in the Yellow River’s primary tributaries: a multi-source data analysis of the Wanchuan River Basin - Liu, Xingyu; Li, Xiaodan; Zhang, Xiaoning; Yang, Jiali; Li, Zizhen; Zhang, Haichao; Liu, Xuelu (Frontiers in Plant Science, 2026)
IntroductionVegetation status and soil moisture play crucial roles in ecosystem supply- demand services. Understanding the spatiotemporal variations of soil moisture (SM) and vegetation conditions is essential for assessing the stability of terrestrial ecosystems. However, the long-term response mechanisms and synergistic relationships between soil moisture and vegetation in the upper Yellow River’s Gansu section remain unclear, introducing uncertainties in evaluating the Loess Plateau ecosystem.MethodsUtilizing multi-source data from the Wanchuan River Basin, a major tributary of the Yellow River, an inversion model was constructed to simulate the spatiotemporal distribution of soil moisture at depths of 0–30 cm.Results and DiscussionThe results reveal a distinct spatial pattern of lower moisture in the northern part and higher moisture in the southern part, with no significant variation across soil depths. A comprehensive vegetation index (VEG) integrating net primary productivity (NPP), leaf area index (LAI), and atmosphere-resistant vegetation index (ARVI) was found to be most suitable for this region. Overall vegetation conditions improved annually, with interannual variation following a normal distribution. Significant interaction between vegetation and soil moisture was observed, with the area of statistically significant positive correlation substantially exceeding that of negative correlation, indicating a synergistic relationship between the two variables. Coupling coordination analysis showed notable seasonal differences: in summer, coordination between SM and VEG was significantly divergent (coordinated in the south, uncoordinated in the north), while in other seasons, the relationship was characterized as marginally coordinated. This suggests a need for continuous structural optimization, with marginal coordination representing the predominant state of the soil moisture– vegetation system in the basin.Variable importance screening using the Giniindex- enhanced random forest algorithm identified land surface temperature and potential evapotranspiration as the dominant factors influencing the soil moisture–vegetation coupling coordination degree. These findings provide valuable data and theoretical support for understanding the synergistic mechanisms between soil, water, and vegetation in the Gansu section of the Yellow River, contributing to more effective ecosystem management strategies in the Loess Plateau region.